ANALYZING THE EFFECT OF RETURN ON ASSETS, RETURN ON EQUITY AND EARNINGS PER SHARE ON MARKET SHARE PRICE: A STUDY OF LQ-45 MINING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Mogonta, Kanedia; Pandowo, Merinda (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Capital market can help company in providing company fund. Investor will invest in capital market in expectation to get profit. Financial ratios can be used by investor to help in analyzing company financial performances. The purpose of this research is to analyze the effect of Return on Assets (ROA), Return on Equity (ROE) and Earnings per Share (EPS) on market share price of LQ-45 mining companies listed on Indonesia Stock Exchange (IDX).The samples used were 7 mining companies that selected with using purposive sampling method and using data for financial report from 2011-2015. By using multiple regression analysis, the result shows that ROA, ROE, and EPS simultaneously have positive significant effect on Market Share Price. Partially, ROA has positive significant effect on market share price, ROE has negative effect on market share price, and EPS not have significant effect on market share price. For investors, they should use ROA as financial performance indicator in investing because ROA has a positive significant effect on market share price. Keywords: ROA,ROE, EPS, market share price